A strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material and preparation method thereof

By introducing strong alkali and sugar alcohol into the phase change heat storage material to form intermolecular hydrogen bonds and introducing light absorbers, the problems of low photothermal conversion efficiency, poor stability and serious energy dissipation in the long-term photothermal energy storage of phase change heat storage materials are solved, and efficient and stable long-term photothermal energy storage is achieved.

CN115491182BActive Publication Date: 2025-03-21SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211140484.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-19
Publication Date
2025-03-21
Estimated Expiration
2042-09-19

AI Technical Summary

Technical Problem

Existing phase-change heat storage materials have problems such as low photothermal conversion efficiency, poor stability and serious energy dissipation in long-term photothermal energy storage across seasons.

Method used

A strong alkali-stable supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material is designed. By introducing strong alkali and sugar alcohol to form intermolecular hydrogen bonds, hindering the movement and crystallization of sugar alcohol molecules, and introducing light absorbers on the basis of not destroying the supercooling stability, achieving efficient photothermal conversion.

Benefits of technology

It achieves efficient photothermal conversion, high energy density, good stability, and maintains a stable supercooling state for more than 360 days at room temperature, thereby storing the absorbed heat energy efficiently for a long time to the maximum extent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115491182B_ABST
    Figure CN115491182B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of energy storage phase change materials, and relates to a strong alkali-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material and a preparation method thereof, wherein the photothermal energy storage composite phase change material includes 85-94 parts by mass of sugar alcohol, 5-10 parts by mass of strong alkali stabilizer, and 1-5 parts by mass of light absorber, and the preparation method is as follows: a certain amount of strong alkali, sugar alcohol and light absorber are dissolved in deionized water in turn to prepare a mixed solution; the mixed solution is heated at a temperature higher than the melting point of the sugar alcohol to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material. The present invention, by means of a strong intermolecular hydrogen bond between a strong alkali and a sugar alcohol material, enhances the crystallization energy barrier of the sugar alcohol material, and hinders the orderly arrangement of the crystals of the sugar alcohol molecules. Without damaging the supercooled stability of the sugar alcohol, a light absorber is introduced, which greatly enhances the light absorption capacity of the phase change composite material, thereby obtaining a stable supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage phase change materials, and in particular to a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material and a preparation method thereof. Background Art

[0002] Thermal energy is one of the indispensable energy sources in people's production and life. As the main representative of clean energy, solar energy and solar thermal technology are the main solutions for directly providing energy to the people in the future. With the continuous advancement and development of technology, short-term and efficient solar thermal storage has taken shape. However, due to the intermittent supply of solar energy and the mismatch of energy supply, short-term thermal energy storage cannot effectively solve the problem of long-term energy supply. Cross-seasonal solar thermal energy storage is a potential and effective means to solve the contradiction of long-term energy supply.

[0003] Phase change thermal storage materials, as an important type of energy storage material with high energy storage density and narrow phase change temperature zone, are widely used in the storage of solar thermal energy. However, the low photothermal absorption capacity of phase change energy storage materials hinders their efficient and direct use of solar energy. At the same time, due to energy interaction with the external environment, heat is severely dissipated during long-term storage across seasons, resulting in low efficiency. Problems such as low photothermal conversion efficiency, poor stability, and severe energy dissipation in cross-seasonal photothermal energy storage have greatly restricted the development of solar thermal technology and are difficult problems that need to be solved urgently.

[0004] Long-term photothermal storage phase change materials are a type of phase change material that can directly achieve efficient photothermal conversion and store thermal energy stably for a long time. Stable supercooled state thermal storage materials are a typical type of long-term phase change thermal storage materials. Without the need for additional insulation, they can store thermal energy efficiently for a long time during the phase change process and can greatly reduce the heat dissipation of the thermal storage material into the environment. However, the research and development of stable supercooled state long-term thermal storage materials with direct photothermal conversion capabilities and high energy density is still a long way to go. Summary of the invention

[0005] In order to solve the problems of low photothermal conversion efficiency, poor stability and serious energy dissipation in long-term photothermal energy storage, the present invention designs a long-term sugar alcohol-based phase change thermal storage composite material with efficient photothermal conversion capability, high energy density and stable supercooled state. A strong base is used as a stabilizer for the sugar alcohol to achieve long-term energy storage in a stable supercooled state. On the basis of not destroying the supercooling stability, a light absorber is further introduced to achieve efficient photothermal conversion. A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material is provided.

[0006] The technical scheme of the present invention is: a strong base stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material, the mass ratio of each component is: 85-94 mass parts of sugar alcohol, 5-10 mass parts of strong base stabilizer, 1-5 mass parts of light absorber, wherein sugar alcohol is a commonly used phase change energy storage material, has a large supercooling degree and a large phase change enthalpy value, the strong base stabilizer forms an intermolecular hydrogen bond with the sugar alcohol, hinders the movement and crystallization of the sugar alcohol molecules, and dopamine is polymerized into polydopamine in an alkaline environment as a light absorber for efficient light absorption, thereby preparing a stable supercooled state heat storage phase change composite material. It can be directly used for photothermal conversion, the light absorption rate exceeds 90%, and the sugar alcohol supercooled state can be stabilized at room temperature for more than one month, thereby realizing long-term photothermal energy storage.

[0007] By adopting the above technical scheme, the sugar alcohol can be one or more of erythritol, mannitol, xylitol, inositol, sorbitol, maltitol and lactitol.

[0008] Preferably, the sugar alcohol is erythritol, mannitol or xylitol.

[0009] The most preferred sugar alcohol is erythritol.

[0010] By adopting the above technical solution, the strong base stabilizer can be one or more of the inorganic strong base sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, ammonium hydroxide, and calcium hydroxide.

[0011] Preferably, the strong base is sodium hydroxide or potassium hydroxide.

[0012] The most preferred strong base is sodium hydroxide.

[0013] Preferably, the light absorber is natural or artificial melanin dopamine and its derivatives. In order to enhance the light-to-heat conversion capability of the phase change material without destroying the supercooling stability of the composite material, the introduced light absorber can form hydrogen bonds with the sugar alcohol, thereby not destroying the long-term heat storage capacity of the phase change composite material. Dopamine has abundant amino, hydroxyl and other chemical groups that can form intermolecular hydrogen bonds, and can achieve direct light-to-heat conversion without destroying the stable supercooling state of the sugar alcohol.

[0014] The present invention also provides a method for preparing a supercooled sugar alcohol-based long-term light-thermal energy storage phase change composite material, comprising the following steps:

[0015] Step (1): dissolving a certain amount of a strong base, a sugar alcohol and a light absorber in deionized water in order according to a certain ratio to prepare a mixed solution;

[0016] Step (2): heating the mixed solution at a temperature higher than the melting point of the sugar alcohol to evaporate the deionized water, thereby preparing a stable supercooled sugar alcohol-based composite phase change material.

[0017] Specifically, the mass fractions of the strong base, sugar alcohol and light absorber in step (1) are 5-10%, 85-94% and 1-5% respectively.

[0018] The preferred mass fractions of the strong base, sugar alcohol and light absorber are: 5%, 94% and 1%.

[0019] Specifically, the heating temperature in step (2) should be 10 to 30° C. higher than the melting point of the sugar alcohol.

[0020] The principle of the present invention is: supercooled long-term heat storage material refers to a special type of phase change material with stable supercooling behavior. In the cooling process after melting, the supercooled phase change material begins to gradually crystallize and release the stored heat energy after a period of relaxation time. By extending the relaxation time of the supercooled material and preparing a stable supercooled phase change material at room temperature, the energy storage efficiency of the phase change material in the long-term heat storage process can be greatly improved. The photothermal energy storage phase change composite material of the present invention has high energy storage efficiency, long aging, and good stability, and does not require additional insulation during the long-term heat storage process, and can also retain the latent heat energy stored in the phase change material to the maximum extent. Sugar alcohol material is a typical supercooled heat storage material. Its large phase change enthalpy, stable phase change behavior and large supercooling degree make it possible to prepare sugar alcohol long-term supercooled heat storage materials. However, the instability of its crystallization brings uncertainty to the high energy efficiency of long-term heat storage.

[0021] The rich hydroxyl functional groups of sugar alcohol phase change materials form a wide range of hydrogen bond networks, which directly affect their melting and crystallization processes. By regulating the hydrogen bond network, the phase change behavior of sugar alcohol materials can be regulated, and then a stable supercooled sugar alcohol long-term heat storage material can be prepared. By introducing a strong base to form intermolecular hydrogen bonds with sugar alcohols, slowing down the movement of sugar alcohol molecules, increasing the crystallization energy barrier, and prolonging the crystallization relaxation time, a long-term stable supercooled sugar alcohol heat storage composite material at room temperature is prepared.

[0022] The beneficial effects of the present invention are: providing a simple and efficient method for preparing a supercooled sugar alcohol-based long-term heat storage phase change composite material, providing a new solution and a new energy storage material for solving the problem of long-term heat storage across seasons. This material is different from previous phase change materials. It can not only directly realize the conversion of photothermal energy, but also maintain a stable supercooled state for more than 360 days at room temperature, thereby maximally storing the absorbed heat energy in the phase change material for a long time and efficiently, providing a new idea and new answer for long-term photothermal energy storage technology.

[0023] The present invention uses the strong intermolecular hydrogen bonding between the strong base and the sugar alcohol material to increase the crystallization energy barrier of the sugar alcohol material and hinder the orderly crystallization of the sugar alcohol molecules. Without damaging the supercooling stability of the sugar alcohol, the light absorber is introduced to greatly improve the light absorption capacity of the phase change composite material, thereby obtaining a sugar alcohol-based long-term light-thermal energy storage phase change composite material in a stable supercooled state. The present invention has simple process, low cost, good stability, low energy consumption, high product yield, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a photo of the crystallinity test experiment of pure erythritol.

[0025] Figure 2 This is a photo of the stability experiment after replacing the light absorber with nano-graphite powder.

[0026] Figure 3 These are photos of the supercooling stability experiment of erythritol composite materials.

[0027] Figure 4 The phase transition behavior of supercooled erythritol composites was tested by DSC.

[0028] Figure 5 Comparison of absorbance of erythritol and erythritol composite material.

[0029] Figure 6 Heat flow variation for erythritol loaded with different contents of sodium hydroxide.

[0030] Figure 7 Changes in enthalpy of loading different contents of sodium hydroxide for erythritol. DETAILED DESCRIPTION

[0031] The following examples are all detailed, clear and complete descriptions of the present invention. Obviously, these examples are only some examples of the scheme of the present invention, not all examples. Based on the implementation examples generated by the present invention, other examples realized by ordinary technicians in this field without making creative work are all within the scope of protection of the present invention.

[0032] A strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material, the mass ratio of each component is: 85-94 mass parts of sugar alcohol, 5-10 mass parts of strong base stabilizer, 1-5 mass parts of light absorber. The preparation method is as follows:

[0033] Step (1): dissolving a certain amount of strong base, sugar alcohol and light absorber in deionized water in sequence according to a mass ratio of 85-94 parts by mass of sugar alcohol, 5-10 parts by mass of strong base stabilizer and 1-5 parts by mass of light absorber to prepare a mixed solution;

[0034] Step (2): heating the mixed solution at a temperature higher than the melting point of the sugar alcohol at 0 to 30° C. to evaporate deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0035] Example 1

[0036] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0037] (1) Preparation of mixed solution: accurately weigh 2 g of erythritol, 0.1 g of sodium hydroxide, and 0.02 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0038] (2) The mixed solution was heated in an oven at 130° C. for 6 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0039] Example 2

[0040] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0041] (1) Preparation of mixed solution: accurately weigh 2 g of erythritol, 0.1 g of sodium hydroxide, and 0.1 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0042] (2) The mixed solution was heated in an oven at 130° C. for 6 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0043] Example 3

[0044] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0045] (1) Preparation of mixed solution: accurately weigh 2 g of erythritol, 0.2 g of sodium hydroxide, and 0.1 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0046] (2) The mixed solution was heated in an oven at 130° C. for 6 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0047] Example 4

[0048] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0049] (1) Preparation of mixed solution: accurately weigh 2 g of erythritol, 0.2 g of potassium hydroxide, and 0.1 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0050] (2) The mixed solution was heated in an oven at 130° C. for 6 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0051] Comparative Example 1

[0052] (1) Preparation of mixed solution: accurately weigh 2 g of erythritol and stir and dissolve it in 20 g of deionized water;

[0053] (2) The mixed solution was heated in an oven at 130° C. for 6 hours to evaporate the deionized water.

[0054] Table 1 Supercooling stability and light absorption properties of erythritol phase change composite materials prepared in Example

[0055]

[0056] Example 5

[0057] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0058] (1) Preparation of mixed solution: accurately weigh 2 g of mannitol, 0.1 g of sodium hydroxide, and 0.02 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0059] (2) The mixed solution was heated in an oven at 160° C. for 5 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0060] Example 6

[0061] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0062] (1) Preparation of mixed solution: accurately weigh 2 g of mannitol, 0.2 g of sodium hydroxide, and 0.1 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0063] (2) The mixed solution was heated in an oven at 160° C. for 5 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0064] Example 7

[0065] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0066] (1) Preparation of mixed solution: accurately weigh 2 g of mannitol, 0.2 g of potassium hydroxide, and 0.1 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0067] (2) The mixed solution was heated in an oven at 160° C. for 5 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0068] Comparative Example 2

[0069] (1) Preparation of mixed solution: accurately weigh 2 g of mannitol and stir to dissolve it in 20 g of deionized water;

[0070] (2) The mixed solution was heated in an oven at 160° C. for 5 hours to evaporate the deionized water.

[0071] Table 2 Supercooling stability and light absorption properties of mannitol phase change composite materials prepared in Example

[0072]

[0073] Example 8

[0074] A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material comprises the following steps:

[0075] (1) Preparation of mixed solution: accurately weigh 2 g of xylitol, 0.1 g of sodium hydroxide, and 0.02 g of dopamine hydrochloride, and stir and dissolve them in 20 g of deionized water;

[0076] (2) The mixed solution was heated in an oven at 120° C. for 8 hours to evaporate the deionized water, thereby obtaining a stable supercooled sugar alcohol-based composite phase change material.

[0077] Comparative Example 3

[0078] (1) Preparation of mixed solution: accurately weigh 2 g of xylitol and stir and dissolve it in 20 g of deionized water;

[0079] (2) The mixed solution was heated in an oven at 120° C. for 8 hours to evaporate the deionized water.

[0080] Table 3 Supercooling stability and light absorption properties of xylitol phase change composite materials prepared in Example

[0081]

[0082] Tables 1 to 3 show the results of the embodiments of the invention. It can be seen from the results of the embodiments and the comparative examples that the phase change composite material prepared by this scheme has good supercooling stability and can achieve stable long-term thermal energy storage. At the same time, the phase change composite material has excellent optical absorption capacity and can efficiently realize photothermal conversion, thereby providing feasibility for long-term storage of direct photothermal energy.

[0083] The accompanying drawings supplement the implementation results of the embodiment.

[0084] Figure 1 This illustrates the inherent supercooling instability of erythritol, which will spontaneously crystallize during the cooling process and cannot stably store heat for a long time at room temperature.

[0085] Figure 2 It is explained that since there is no hydrogen bond interaction between nano-graphite powder and sugar alcohol, its addition will destroy the supercooling stability of the composite material.

[0086] Figure 3 The stable supercooled heat storage performance of the erythritol composite material prepared in the example at room temperature is illustrated.

[0087] Figure 4 It is described that after storing heat for one year, the erythritol composite material prepared according to the example can still release the stored heat energy.

[0088] Figure 5 A comparison chart of the light absorption capacity of the erythritol composite material prepared according to the example and pure erythritol is presented, indicating that the composite material prepared by the inventive scheme has good light absorption capacity.

[0089] Figure 6 , Figure 7 The DSC curves of the effects of different contents of sodium hydroxide on the solid-liquid phase transition behavior of erythritol composites are described. As the content of sodium hydroxide increases, the enthalpy of the composite material gradually decreases.

[0090] The above examples are summaries of the most preferred examples shown in the present invention, but the protection field of the present invention does not only include these. Any non-original modifications and improvements by technicians in this field based on the principles and solutions of the present invention should be included in the protection scope of the present invention.

Claims

1. A strong base-stable supercooled sugar alcohol-based long-term photothermal energy storage composite phase change material, characterized in that: The invention comprises 85-94 parts by weight of sugar alcohol, 5-10 parts by weight of a strong base stabilizer and 1-5 parts by weight of a light absorber. The preparation method comprises the following steps: dissolving the strong base stabilizer, the sugar alcohol and the light absorber in deionized water in sequence to prepare a mixed solution, wherein the light absorber is dopamine hydrochloride and the strong base stabilizer is an inorganic strong base, which is one or more selected from the group consisting of sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, ammonium hydroxide and calcium hydroxide; and heating the mixed solution at a temperature higher than the melting point of the sugar alcohol to evaporate the deionized water, thereby preparing a stable supercooled sugar alcohol-based composite phase change material.

2. The strong base-stable supercooled sugar alcohol-based long-term photothermal energy storage composite phase change material according to claim 1, characterized in that: The sugar alcohol is one or more of erythritol, mannitol, xylitol, inositol, sorbitol, maltitol and lactitol.

3. The strong base-stable supercooled sugar alcohol-based long-term photothermal energy storage composite phase change material according to claim 2, characterized in that: The sugar alcohol is erythritol.

4. The strong base-stable supercooled sugar alcohol-based long-term photothermal energy storage composite phase change material according to claim 2, characterized in that: The strong base stabilizer is sodium hydroxide.

5. A method for preparing a strong base-stabilized supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material, characterized in that: The steps include: Step (1): dissolving 5-10 parts by weight of a strong base stabilizer, 85-94 parts by weight of a sugar alcohol, and 1-5 parts by weight of a light absorber in deionized water in order according to a certain ratio to prepare a mixed solution; the light absorber is dopamine hydrochloride, and the strong base stabilizer is an inorganic strong base, selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, ammonium hydroxide, and calcium hydroxide; Step (2): heating the mixed solution at a temperature higher than the melting point of the sugar alcohol to evaporate the deionized water, thereby preparing a stable supercooled sugar alcohol-based composite phase change material.

6. The method for preparing a strong base-stable supercooled sugar alcohol-based long-term light-thermal energy storage phase change composite material according to claim 4, characterized in that: The mass fractions of the strong base stabilizer, sugar alcohol, and light absorber are 5%, 94%, and 1%, respectively.

7. The method for preparing a strong base-stable supercooled sugar alcohol-based long-term photothermal energy storage phase change composite material according to claim 4, characterized in that: The heating temperature in step (2) should be 10-30°C higher than the melting point of the sugar alcohol.

Citation Information

Patent Citations

  • Medium-temperature organic phase-change heat storage material and preparation method thereof

    CN112409995A

  • Heat storage material composition, heat storage device, and heat storage method

    US20160090520A1